A face-based immersed boundary method for compressible flows using a uniform interpolation stencil - Kasturi Rangan, M. L. N. V.; Ghosh, Santanu (Frontiers in Mechanical Engineering, 2022)
In this paper, an immersed-boundary method developed for compressible viscous flows (Ramakrishnan, R., Girdhar, A., & Ghosh, S. (2016). Immersed Boundary Methods for Compressible Laminar Flows.) is modified to improve its stability and robustness. The embedded object is represented as a set of line segments in two dimensions with their outward unit normal vectors specified. A forcing method that leverages the finite-volume approach is used, wherein the solution at cell interfaces that lie near the boundaries of the embedded solid is reconstructed to implicitly satisfy boundary conditions at the immersed surface. An interpolation point is constructed along the normal to the immersed surface to achieve this. The proposed immersed boundary method is validated for transonic inviscid flow past a bump in a channel, supersonic flow past a circular cylinder, transonic viscous flow past a NACA0012 airfoil and supersonic viscous flow past a circular cylinder. The results are compared with simulations from literature using contours of flow properties, surface pressure or Mach number plots, and show good agreement.